Elektroninės valdžios diegimas ir perspektyvos Lietuvoje: visuomenės ir valdžios institucijų sąveika - Limba, Tadas (Information & Media, 2008)
Straipsnyje analizuojami elektroninės valdžios įgyvendinimo teoriniai aspektai ir problematika, atskleidžiamos valdžios institucijų bendravimo elektroniniu paštu teorinės ir praktinės spragos, aptariamos elektroninės valdžios institucinio įgyvendinimo ir reguliavimo perspektyvos.Implementation and perspectives of electronic governance in Lithuania: the society interaction with public administrationTadas LimbaSummaryThe paper analyses the implementation of electronic governance and its perspective, some aspects of society interaction with public administration in Lithuania. The main principles of electronic governance creation as well as the resistance of electronic governance development from the point of view of public sector are discussed. The questions of peculiarities and assessment of the level of implementation of the e-government legal regulations are discussed, too. The author of the article suggests that the public administration and legal environment of e-governance is of crucial importance to the development of the knowledge society and knowledge economy, also, for the adaptation of the governmental bodies to the changing societal needs. The aim of this paper is to: (1) identify the issues of implementation of electronic government, the tendencies of electronic governance development in Lithuania; (2) analyse some questions of interaction between society and governanceby e-mail; (3) discuss the institutional aspects and perspectives of electronic governance development;(4) provide some recommendations.